2010
DOI: 10.1111/j.1751-2980.2010.00441.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus‐induced liver fibrosis and cirrhosis: The value of liver and spleen volumetry with multi‐detector spiral computed tomography

Abstract: Variations in liver and spleen volume correlated with the degree of liver fibrosis and cirrhosis and could be used in the non-invasive follow-up of the development of liver fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 44 publications
(74 reference statements)
0
14
1
Order By: Relevance
“…The study showed that LMV and RV decreased from stage 2 to 4, and this finding could be explained by the enlarged range of liver fibrosis and growth of fibrous septa from the expanded portal triad into the surrounding hepatic parenchyma of left medial liver lobe and right liver lobe resulting in atrophy of these liver lobes [22]. Our results were inconsistent with the published report [23] that LMV and RV decreased with the progress of liver fibrosis from stage 0 to 4 when the fibrosis was staged with the Ishak pathologic scoring system. It is the different pathologic scoring system that could explain the inconsistency of our findings with this published article.…”
Section: Discussioncontrasting
confidence: 90%
“…The study showed that LMV and RV decreased from stage 2 to 4, and this finding could be explained by the enlarged range of liver fibrosis and growth of fibrous septa from the expanded portal triad into the surrounding hepatic parenchyma of left medial liver lobe and right liver lobe resulting in atrophy of these liver lobes [22]. Our results were inconsistent with the published report [23] that LMV and RV decreased with the progress of liver fibrosis from stage 0 to 4 when the fibrosis was staged with the Ishak pathologic scoring system. It is the different pathologic scoring system that could explain the inconsistency of our findings with this published article.…”
Section: Discussioncontrasting
confidence: 90%
“…Quantitative measurement of LSN on routine CT images accurately differentiated cirrhotic from noncirrhotic livers and was highly reproducible. (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Severe LSN in the setting of CLD strongly indicates cirrhosis and can obviate biopsy in some cases.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that measuring the LV is a useful tool for estimating liver function and that a decrease of the liver volume comes along with the progression of liver cirrhosis3637. Moreover, Hashimoto and Watanabe et al .…”
Section: Discussionmentioning
confidence: 99%